Feasibility Study and Preliminary Results of Prognostic Value of Bone SPECT-CT Quantitative Indices for the Response Assessment of Bone Metastatic Prostate Carcinoma to Abiraterone - Romain de Laroche; David Bourhis; David Bourhis; David Bourhis; Philippe Robin; Philippe Robin; Philippe Robin; Olivier Delcroix; Olivier Delcroix; Solène Querellou; Solène Querellou; Solène Querellou; et al. (Frontiers in Medicine, 2020)
Objective: We assessed the prognostic value of quantitative indices extracted from bone SPECT-CT to evaluate the response of bone metastatic castrate-resistant prostate cancer (BmCRPC) to abiraterone.Methods: Consecutive patients with BmCRPC initiating treatment with abiraterone from March 2014 to March 2015 were prospectively included. Three 2-bed SPECT-CT [at baseline [M0], after 3 months [M3], and 6 months [M6] of treatment], were planned (Symbia Intevo®, Siemens). SPECT data were reconstructed using an Ordered Subset Conjugate Gradient Minimization (OSCGM) algorithm allowing SUV quantification. SUVmax and SUVpeak of the highest uptake lesion were measured in each SPECT-CT. Total Neoplastic Osteoblastic Metabolic Volume (NOMV) was assessed. PSA level was recorded at baseline, M3, and M6 of treatment. Overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS) were calculated.Results: Nineteen patients aged 71.1 ± 7.7 years were included. Low M0 SUVmax was significantly predictive of longer OS (p = 0.04). Low NOMV at M0 were significantly predictive of longer PFS (p = 0.02). Patients with increase of at least 12.5% of the SUVpeak of the highest uptake lesion between M0 and M3 (ΔSUVpeakM0M3) had a significantly longer OS (p = 0.03). Patients with increase (or decrease lesser than 25%) of ΔSUVpeakM0M3 had a significantly longer DSS (p = 0.01). Patients with increase of NOMV of at least 45% between M0 and M6 had a significantly shorter PFS (p < 0.001). Variations of NOMV between M0 and M6 were significantly correlated with PSA variations between M0 and M6 (rs = 0.73, p = 0.02).Conclusions: Quantitative bone SPECT-CT appears to be a promising tool of BmCRPC assessment. Early flare-up phenomenon seems to predict longer OS.